Utilitarian VS Hedonic Value: Which is More Influential for Indonesian Consumers in Increasing Purchase Intention in E-Commerce? - Nisrina Sherin Caesalpinia; Bethani Suryawardani (Journal of Consumer Sciences, 2025)
Background: Companies should leverage the rapid growth of online shopping in Indonesia to enhance customer experiences and boost sales. Live streaming plays a crucial role in influencing customer behavior, making it a valuable strategy for increasing purchasing interest. Purpose: This study examined how purchase intention in e-commerce is affected by utilitarian and hedonic values, mediated by trust in the seller. Method: A quantitative approach employed purposive sampling to select 210 participants as the primary data source for this study. The collected data were evaluated utilizing a five-point Likert scale and analyzed using the Structural Equation Modeling (SEM). Findings: The findings revealed that utilitarian value had no impact on trust in the seller of live-streamed fashion products on Shopee, whereas hedonic value had a significant impact. Additionally, the factor with the greatest impact on purchase intention was trust in the seller. In contrast, purchase intention was significantly influenced by hedonic value, which was mediated by trust in the seller. Conclusions: Trust in the seller is crucial in shaping purchase intentions within live streaming e-commerce, mainly when influenced by hedonic value. This highlights the importance of brands strengthening their utilitarian value while prioritizing emotional engagement to foster customer trust and drive sales. Research implication: The Theoretical contribution of this study lies in integrating the Theory of Planned Behavior (TPB) with the concept of customer perceived value (CPV), which has rarely been studied in previous literature. The practical implications for e-commerce businesses is the importance of establishing trust in the seller to strengthen purchase intentions.